Video-based on-ward supervision for final year medical students. Issue 1 (December 2015) - Groener, JB; Bugaj, TJ; Scarpone, R.; Koechel, A.; Stiepak, J.; Branchereau, S.; Krautter, M.; Herzog, W.; Nikendei, C.
Abstract Background Constructive feedback is an essential element of the educational process, helping trainees reach their maximum potential and increasing their skill level. Video-based feedback has been described as highly effective in various educational contexts. The present study aimed to evaluate the feasibility and acceptability of video-based, on-ward supervision for final year students in a clinical context with real patients. Methods Nine final year medical students (three male, six female; aged 25.1 ± 0.7 years) and eight patients (five male, three female; aged 59.3 ± 16.8 years) participated in the pilot study. Final year students performed routine medical procedures at bedside on internal medicine wards at the University of Heidelberg Medical Hospital. Students were filmed and were under supervision. After performing the procedures, an oral feedback loop was established including student, patient and supervisor feedback on communicative and procedural aspects of skills performed. Finally, students watched their video, focusing on specific teachable moments mentioned by the supervisor. Written evaluations and semi-structured interviews were conducted that focused on the benefits of video-based, on-ward supervision. Interviews were analysed qualitatively, using open coding to establish recurring themes and overarching categories to describe patients' and students' impressions. Descriptive, quantitative analysis was used for questionnaire data. Results Supervised, self-chosen skills included history taking (n = 6), physical examination (n = 1), IV cannulation (n = 1), and ECG recording (n = 1). The video-based, on-ward supervision was well accepted by patients and students. Supervisor feedback was rated as highly beneficial, with the video material providing an additional opportunity to focus on crucial aspects and to further validate the supervisor's feedback. Students felt the video material would be less beneficial without the supervisor's feedback. The setting was rated as realistic, with filming not influencing behaviour. Conclusion Video-based, on-ward supervision may be a powerful tool for improving clinical medical education. However, it should be regarded as an additional tool in combination with supervisors' oral feedback. Acceptance was high in both students and patients. Further research should address possibilities of efficiently combining and routinely establishing these forms of feedback in medical education.